Development of criterion for comparative assessment of executive systems functional actvity - Serdiuk, Olga (Technology audit and production reserves, 2016)
In this paper, the general principles of the comparative assessment of the results of procedural activity for objects of executive systems are developed. The system of determining the baseline, relying on that provides accounting of all influencing factors and the possibility of developing a common assessment criterion are proved. An assessment indicator that takes into account all the relevant input and output parameters, and allows comparative assessment of procedural activities of objects of executive systems is developed. Versatility of developed indicator is demonstrated by the comparative assessment of the professional abilities of the subjects and in the decision of selecting the best variant of equipment. Also it is developed a method that compensates for the inequality of expert assessments of input products when assessing the functionality of ES objects. The proposed approach gives the possibility of using common assessment criteria and a common method of reducing the baseline to identify the results of operations of the technical facilities (equipment) and the staff.